2005
DOI: 10.1038/ng1509
|View full text |Cite|
|
Sign up to set email alerts
|

Low LDL cholesterol in individuals of African descent resulting from frequent nonsense mutations in PCSK9

Abstract: The low-density lipoprotein receptor (LDLR) prevents hypercholesterolemia and atherosclerosis by removing low-density lipoprotein (LDL) from circulation. Mutations in the genes encoding either LDLR or its ligand (APOB) cause severe hypercholesterolemia. Missense mutations in PCSK9, encoding a serine protease in the secretory pathway, also cause hypercholesterolemia. These mutations are probably gain-of-function mutations, as overexpression of PCSK9 in the liver of mice produces hypercholesterolemia by reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
801
3
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,267 publications
(837 citation statements)
references
References 19 publications
18
801
3
15
Order By: Relevance
“…The use of a multiethnic population for resequencing capitalizes on genetic variation that arises from ethnic differences in population history. Previously, in the Dallas Heart Study we found highly informative sequence variants in PCSK9 and NPC1L1 that were largely confined to African Americans [18][19][20] . In contrast, the ANGPTL4 variants identified in this study were more informative in European Americans.…”
mentioning
confidence: 93%
“…The use of a multiethnic population for resequencing capitalizes on genetic variation that arises from ethnic differences in population history. Previously, in the Dallas Heart Study we found highly informative sequence variants in PCSK9 and NPC1L1 that were largely confined to African Americans [18][19][20] . In contrast, the ANGPTL4 variants identified in this study were more informative in European Americans.…”
mentioning
confidence: 93%
“…[13][14][15] Missense mutations of PCSK9 associated with hypercholesterolemia in humans would increase the capacity of PCSK9 to limit the number of LDL-r, thus representing gain of function mutations. In sharp contrast, mice with targeted inactivation of PCSK9 gene (pcsk9 Ϫ/Ϫ ) have an increased number of LDL-r in the liver, increased removal of plasma LDL, and reduced plasma LDL-C. 16 In 2005 Cohen et al 17 found that 2 inactivating mutations of PCSK9 (Y142X and C679X), present in 2% to 2.6% of blacks of the Dallas Heart Study, were associated with 30% to 40% reduction of plasma LDL-C. They proposed the concept that in human loss of function mutations of PCSK9 would increase the number of liver LDL-r and the receptor mediated uptake and catabolism of plasma LDL, as observed in pcsk9 Ϫ/Ϫ mice.…”
mentioning
confidence: 99%
“…20 In addition, PCSK9 mutation has been linked to accelerated ApoB production, 21 and can worsen the phenotype of heterozygous FH. 22 One of the PCSK9 variants we found in this patient was previously, though not definitively, linked to alterations in cholesterol levels; it was initially associated with elevated cholesterol, but a subsequent, larger study in African Americans linked it with both unusually high and unusually low LDL cholesterol values.…”
Section: Discussionmentioning
confidence: 99%